Blockchain Technology in Supply Chain Management A Survey of Applications Challenges and Opportunities - J Raja; D Ruba; V Sai Krishna; K Manasa; Tiwari Mohit; Koilraj Thomas (ITM Web of Conferences)
Blockchain technology has become a disruptive force that is quickly reshaping supply chain management by providing greater transparency, security, and efficiency. As promising as the Blockchain is, previous research fails to provide solutions for bringing Blockchain into real-world practice, for getting it up to mass scale, and for ensuring that it meets the regulators’ requirements and these factors limit a more widespread adoption of Blockchain. By offering a review of blockchain-based supply chain management initiatives, their pros and cons, and addressing under-researched topics related to optimized consensus mechanisms, interoperability solutions, and AI-driven solutions integration, this research fills the gaps to decrease inefficiencies in supply chains. As part of the latter, the study presents zero-knowledge proofs, decentralized identity verification and cross-chain protocols as potential solutions to address security concerns and enhance interoperability among multiple chains. Also, a deeper implementation roadmap is provided, enabling pragmatic applicability in real business operations across the global supply chain. By analyzing cases, the study emphasizes the practical contributions of blockchain in traceability, fraud prevention, inventory optimization, and automated contract execution. The results highlight blockchain as a scalable, secure, and legally compliant technology for solving modern supply chain problems, filling the gap between theory and practical adoption.